Enhancing outcomes: neurosurgical resection in brain metastasis patients with poor Karnofsky performance score - a comprehensive survival analysis - Goldberg, Maria; Mondragon-Soto, Michel G.; Altawalbeh, Ghaith; Baumgart, Lea; Gempt, Jens; Bernhardt, Denise; Combs, Stephanie E.; Meyer, Bernhard; Aftahy, Amir Kaywan (Frontiers in Oncology, 2024)
Background: A reduced Karnofsky performance score (KPS) often leads to the discontinuation of surgical and adjuvant therapy, owing to a lack of evidence of survival and quality of life benefits. This study aimed to examine the clinical and treatment outcomes of patients with KPS < 70 after neurosurgical resection and identify prognostic factors associated with better survival. Methods: Patients with a preoperative KPS < 70 who underwent surgical resection for newly diagnosed brain metastases (BM) between 2007 and 2020 were retrospectively analyzed. The KPS, age, sex, tumor localization, cumulative tumor volume, number of lesions, extent of resection, prognostic assessment scores, adjuvant radiotherapy and systemic therapy, and presence of disease progression were analyzed. Univariate and multivariate logistic regression analyses were performed to determine the factors associated with better survival. Survival > 3 months was considered favorable and ≤ 3 months as poor. Results: A total of 140 patients were identified. Median overall survival was 5.6 months (range 0-58). There was no difference in the preoperative KPS between the groups of > 3 and ≤ 3 months (50; range, 20-60 vs. 50; range, 10-60, p = 0.077). There was a significant improvement in KPS after surgery in patients with a preoperative KPS of 20% (20 vs 40 ± 20, p = 0.048). In the other groups, no significant changes in KPS were observed. Adjuvant radiotherapy was associated with better survival (44 [84.6%] vs. 32 [36.4%]; hazard ratio [HR], 0.0363; confidence interval [CI], 0.197-0.670, p = 0.00199). Adjuvant chemotherapy and immunotherapy resulted in prolonged survival (24 [46.2%] vs. 12 [13.6%]; HR 0.474, CI 0.263-0.854, p = 0.013]. Systemic disease progression was associated with poor survival (36 [50%] vs. 71 [80.7%]; HR 5.975, CI 2.610-13.677, p < 0.001]. Neurosurgical resection is an appropriate treatment modality for patients with low KPS. Surgery may improve functional status and facilitate further tumor-specific treatment. There is almost no information regarding surgical and adjuvant treatment in patients with low KPS. Our paper provides novel data on clinical outcome and survival analysis of patients with BM who underwent surgical treatment.